Bank credit extension to the private sector and inflation in South Africa - Dlamini, Samuel Nkosinathi (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2009)
This study investigates the contribution of bank credit extension to the private sector to inflation in South Africa, covering the period 1970:1-2006:4. The long-run impact of bank credit on inflation is investigated by means of the Johansen co integration model. The short-run ynamics of the inflation is subsequently modelled by means of the Vector Error Correction Model (VECM). Using the Johansen methodology, the study identifies two co integrating equations linking inflation and its eterminants. The results suggest that the long-run relationship between inflation and bank credit to the private sector is negative and statistically significant at 10% level. The determinants that are significant at 5% level are: money supply, real gross domestic product, the money market rate, rand/dollar exchange rate and imports. The results are consistent with previous findings. The speed of adjustment in response to deviation from the equilibrium path was found to be negative at 10.56% per quarter, which is consistent with findings by Ohnsorge and Oomes (2003) for Russia. Both the signs and the magnitude of the coefficients suggest that the co integrating vector describes a long-run inflation equation. The impulse response functions confirm the theoretical expectations except for the import prices. The most persistent and significant shocks observed are on impulse response functions of money supply and bank credit to the private sector. The variance decomposition results also suggest that inflation responds quicker to innovations from money supply and the money market rate. The overall results provide evidence that the surge in inflation is associated with an increase in money supply as well as the instability in exchange rate. The effects of exchange rate fluctuation on inflation are reflected through changes in import prices. Based on the results we conclude that an increase in bank credit during the period 1970:1-2006:4 had a negative mpact on inflation in South Africa.
Keywords: Bank loans -- South Africa; Inflation (Finance) -- South Africa; Money supply -- South Africa; Interest rates -- South Africa; Banks and banking -- South Africa; Foreign exchange rates -- South Africa